Effect of Employee Competency and Engagement on Employee Performance of Sharia Bank Sumselbabel KCP UIN Raden Fatah Palembang - Suryani Triana Oktavia; Susi Handayani; M Kurniawan D.P (International Journal of Marketing & Human Resource Research, 2022)
This study aims to analyze the influence of competence and employee involvement on employee performance of Bank Sumsel Babel Syariah KCP UIN Raden Fatah Palembang. The data used in this study came from a questionnaire which filled by 50 respondents. The method of analysis in this study is multiple linear regression analysis. The results of the study prove that competence has a significant positive effect on employee performance. Employee involvement is proven to have a partial significant effect on employee performance. This research is useful for companies to improve employee performance through competence and employee involvement